HUBUNGAN ANTARA KETERAMPILAN SOSIAL DAN KESULITAN BELAJAR PADA ANAK SD: PERSPEKTIF PSIKOLOGI PENDIDIKAN - NOVRIANDI NURSIDIN; Hafizul , Rahmathul Dilfa; Wahyuni Safitri , Hafiz Hidayat (STKIP Subang, 2025)
This study aims to examine the relationship between social skills and learning difficulties in elementary school children from the perspective of educational psychology through a literature review method. The findings indicate that well-developed social skills play a crucial role in enhancing children’s communication abilities, motivation, and active participation in the learning process. Conversely, underdeveloped social skills often contribute to social isolation, anxiety, and emotional barriers that exacerbate learning difficulties. Educational psychology-based interventions focusing on social skills development, such as social-emotional learning and group-based methods, have proven effective in addressing these issues. Therefore, integrating social skills development programs into the elementary school curriculum and fostering collaboration among teachers, parents, and educational psychologists are essential to support children’s holistic learning success.